The road to breast cancer screening with diffusion MRI - Iima, Mami; Le Bihan, Denis (Frontiers in Oncology, 2023)
Breast cancer is the leading cause of cancer in women with a huge medical, social and economic impact. Early diagnosis can be obtained through screening with mammography (MMG) which has been the gold standard method because it is relatively cheap and widely available. Still, MMG suffers from some limitations, such as exposure to X-rays and difficult interpretation in dense breasts. Among other imaging methods, MRI has clearly the highest sensitivity and specificity, and breast MRI is the reference to investigate and manage suspicious lesions revealed by MMG. Despite those performances, MRI which does not rely on X-rays, is not used for screening except for a category of well-defined women at risk due to a high cost and a limited availability. Furthermore, the standard breast MRI approach relies on the injection of gadolinium based contrast agents (GBCA), which have their own risks and contraindications and may lead to long-terms deposits of gadolinium in tissues, including the brain, when examinations are repeated. On the other hand, breast diffusion MRI which gives information on tissue microstructure and tumor perfusion without the need for contrast agents, has been shown to provide a higher specificity than GBCA MRI with a similar sensitivity, above that of MMG. Diffusion MRI thus appears as a promising alternative approach for breast cancer screening, with the main goal of eliminating the existence of a life-threatening lesion with a very high probability. To reach this goal, there is a need first for standardization of diffusion MRI acquisition and data analysis protocols which have been found to vary largely among sites. Second, accessibility and cost-effectiveness of MRI examinations must improve dramatically, which might become possible with the development of dedicated breast screening MRI units operating at low field. In this article, we first review the principles and the current status of breast diffusion MRI, comparing its clinical performance with MMG and GBCA MRI. We then look at how breast diffusion MRI could be implemented and standardized to give optimized accuracy in results. Finally, we examine how a low-cost dedicated breast MRI system prototype could be implemented and brought to the healthcare market.